Book Notes [28, Fall 1991] - Palmer, Bryan D. (Labour / Le Travail, 1991)
The article briefly reviews "Canadian and Australian Labour History," edited by Gregory S. Kealey and Greg Patmore, "Brother Max: Labour Organizer and Educator," by Max Swerdlow, edited by Gregory S. Kealey, "The New Era of Global Competition: State Policy and Market Power." edited by Daniel Drache and Meric S. Gertler, "Making a Middle Class: Student Life in English Canada during the Thirties," by Paul Axelrod, "Careless at Work: Selected Canadian Historical Studies," by J.M.S. Careless, "The Political Economy of Manitoba," edited by Jim Silver and Jeremy Hull, "Debating Canada's Future: Views from the Left," edited by Simon Rosenblum and Peter Findlay, "Activists and Advocates: Toronto's Health Department, 1883-1983," by Heather MacDougall, "Perspectives on Canadian Economic Development: Class, Staples, Gender, and Elites," edited by Gordon Laxer, "The Upper Ottawa Valley to 1855," edited by Richard M. Reid, "Women and Social Change: Feminist Activism in Canada," edited by Jeri Dawn Wine and Janice L. Ristock, "Delivering Motherhood: Maternal Ideologies and Practices in the 19th and 20th Centuries," edited by Katherine Amup, Andrée Levesque, and Ruth Roach Pierson, "Radical Sociologists and the Movement: Experiences, Lessons, and Legacies," edited by Martin Oppenheimer, Martin J. Murray, and Rhonda F. Levine, "Fire in the Hearth: The Radical Politics of Place in America; The Year Left, IV," edited by Mike Davis et al., "The Sociogenesis of a Race Riot: Springfield, Illinois, in 1908," by Roberta Senechal, "American Immigrants and Their Generations: Studies and Commentaries on the Hansen Thesis after Fifty Years," edited by Peter Kivisto and Dag Blanck, "Working Time in Transition: The Political Economy of Working Hours in Industrial Nations," edited by Karl Hinrichs, William Roche, and Carmen Sirianni, "Dependent Care and the Employee Benefits Package: Human Resources Strategies for the 1990s," by LouEllen Crawford, "Learning About Women: Gender, Politics, and Power," edited by Jill K. Conway, Susan C. Bourque, and Joan Scott, "Opera Muliebria: Women and Work in Medieval Europe," by David Herlihy, "Fin de Siècle Socialism; and Other Essays," by Martin Jay, "History and Communications: Harold Innis, Marshall McLuhan, and the Interpretation of History," by Graeme Patterson, "Marx's Proletariat: The Making of a Myth," by David W. Lovell, and "Ideology and Class Conflict in Jamaica: The Politics of Rebellion," by Abigail B. Bakan.